Kinetics of Aluminium Sulfate Synthesis from Pharmaceutical Blister Foil Waste - Akbar Pradana Juliawan Rozak; Bernardus Dwi Tamtomo; Caecilia Pujiastuti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study examines the kinetics of aluminium sulfate (Al?(SO?)?) synthesis from pharmaceutical blister foil waste. The objective is to determine the reaction order, evaluate the effect of temperature on the reaction rate constant, and calculate the activation energy. The process involves dissolving aluminium in KOH, followed by reaction with H?SO? at 60–100°C for 20–60 minutes. The results show that conversion increases with higher temperature and longer reaction time. Kinetic analysis indicates that the reaction follows a first-order model with high linearity (R² = 0.9697–0.9974). The calculated activation energy is -4.506 kJ/mol, suggesting a rapid reaction with a low energy barrier, although deviations from the Arrhenius trend were observed. These findings highlight the potential use of blister foil waste as a raw material for aluminium sulfate production and provide insight into its reaction kinetics. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and Sanitation; SDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production